Analysis of Soil Physical Properties in Sifalago Gomo Village, Boronadu District: Analisa Sifat Fisis Tanah Di Desa Sifalago Gomo Kecamatan Boronadu - Rini; Hani, Sheila (LPPM UPMI, 2023)
Soil is one of the construction materials that has an important role in holding the load of the structure it carries. For this reason, it is necessary to carry out a soil investigation first to determine the ability of the soil to carry the burden of construction in the future. As was done in this study with the aim of analyzing the physical and mechanical properties of the soil which was carried out in the village of Sifalago Gomo, Boronadu District, South Nias Regency. The research method used in this research is qualitative research. From the research conducted, it was found that the soil type is silt clay or belongs to the soil groups A-4 and A-6. This land can be used as embankment (ordinary fill) in road construction as landfill because the CBR value exceeds the provisions of the 2018 division 3 specification, namely the CBR value for ordinary embankment (soil) is a minimum of 6%, namely the CBR value obtained is 7.96%. Provisions for the classification of soil as a silt clay soil type are obtained based on a plasticity index that exceeds 11% and passes sieve No.200 (0.075 mm) exceeding 75%, with a plasticity index value of 11.79%. USCS is a soil classification system that is categorized into two main categories, namely coarse-grained soils consisting of gravel and sand where less than 50% of the soil passes sieve number 200. And fine-grained soils where more than 50% of the soil passes sieve No. 200, namely with a passing value of 94.23%.